Dentists' acceptance of the implementation of electronic medical records at community health centres in Padang City: Penerimaan dokter gigi terhadap penerapan rekam medik elektronik pada pusat kesehatan Masyarakat di Kota Padang - Dea Ignacia Manurung; Intan Batura Endo Mahata; Ricky Amran; Valendriyani Ningrum; Fredy Rendra Taursia Wisnu (Makassar Dental Journal PDGI Makassar, 2026)
The implementation of electronic medical records (EMR) in health facilities, including community health centres, is one strategy to improve the quality of health services, although the level of implementation is still very low, at only 8.0% of 9,831 community health centres. Most community health centres (48.9%) still use non-electronic medical records, while 43.1% use a combined electronic and non-electronic medical record system. However, the level of acceptance of this technology by dentists remains a challenge, especially in areas with limited infrastructure and training. This quantitative study analy-sed the acceptance of dentists towards the implementation of EMR in community health centres in Padang City, using a descriptive survey through a cross-sectional approach on 45 dentists at the Padang City Community Health Centre. The questionnaire was designed to measure dentists' perceptions, atti-tudes, interest, and actual use of EMR. The results showed that 86.7% of respondents perceived EMR as beneficial, with the majority of dentists believing that EMR can improve work efficiency and service quality. Attitudes towards the use of RME were generally positive (95.6%), interest in the implementa-tion of RME was also high (95.6%), and the actual use of RME showed good results (86.7%), although the perception of ease of use was still low. It was concluded that the implementation of RME among dentists had the highest level of acceptance, namely in the good category.